Safeguarding Quality of Higher Education in the Netherlands: Closing the Gap between Policy and Research - Joop Hartog (Center for Economic Studies and ifo Institute (CESifo), 2016)
I will outline the institutional structure of monitoring and improving the quality of higher education in The Netherlands. After critical assessment of recent educational policies a Parliamentary Committee of Inquiry proclaimed the rule of Evidence Based Interventions Only. From discussion and follow-up on that report I will draw the conclusion that more is needed than just a list of recommendations.
Keywords: I23; I28; 330; education; quality monitoring; education policy